TITANIUM MESH APLICATION ON ANTERIOR ALVEOLAR PROCESS AUGMENTATION PROCEDUR : A CASE REPORT - Fathurrahman, Helmi; Hudyono, Rikko (Odonto : Dental Journal, 2020)
Background: Bone reconstruction in a dental implant is a big challenge work, especially in a large defect where there was no anatomic supporting tissue. Nowadays there is no ideal membrane to be considered. In this case, titanium, even though second surgery is needed, seems the best choice as it can maintain its shape under the flap. Titanium may cause a membrane perforation on the mucosa in a thin gingival phenotype case. Purpose: This case report aimed to present a bone reconstruction procedure using 3D titanium membranes for dental implant treatment. Case. A 37 years old male patient came to the clinic with a chief complaint was a defect on his anterior tooth. Intraoral examination revealed an 11 fractured and luxated. Methode and Treatment Result: We used an allograft covered with 3D Titanium mesh after loading a dental implant. At the end of the surgery, a resorbable membrane was applied. Conclusion: It is concluded that 3D Titanium mesh can be an application for anterior bone reconstruction.